2016
DOI: 10.1370/afm.1904
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Patient Behavior Change: Approaches Used by Primary Care Clinicians Whose Patients Have an Increase in Activation Levels

Abstract: PURPOSE We aimed to identify the strategies used to support patient behavior change by clinicians whose patients had an increase in patient activation.METHODS This mixed methods study was conducted in collaboration with Fairview Health Services, a Pioneer Accountable Care Organization. We aggregated data on the change in patient activation measure (PAM) score for 7,144 patients to the primary care clinician level. We conducted in-depth interviews with 10 clinicians whose patients' score increases were among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
88
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 53 publications
2
88
0
2
Order By: Relevance
“…45 A good patient-provider relationship contributed to positive SM support, improved engagement, and higher level of activation in SM behaviors. 22,46 We previously reported that the participants in our intervention group had significant improvement in SM behaviors. However, the analysis showed the mediating effect of patient activation did not contribute to the group difference in SM behavior at 3 months of intervention.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…45 A good patient-provider relationship contributed to positive SM support, improved engagement, and higher level of activation in SM behaviors. 22,46 We previously reported that the participants in our intervention group had significant improvement in SM behaviors. However, the analysis showed the mediating effect of patient activation did not contribute to the group difference in SM behavior at 3 months of intervention.…”
Section: Discussionmentioning
confidence: 67%
“…We speculate that the improvement of SM behaviors in the intervention group may be the result of effective patient-provider relationships as they are known to: 1) empower patients' engagement in self-care; 2) promote close supervision and feedback related to SM behavior adherence; 3) promote positive feedback and encouragement; 4) boost effectiveness of counseling and education; and 5) assist in developing effective coping strategies. 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Recommended topics of discussion include the risks of life-long use disorders and the risk posed to family members if prescription painkillers are intentionally or unintentionally shared. Although communication-based techniques have been shown to improve patient behaviors, 2 the CDC guidelines note that no evidence currently exists to evaluate the effectiveness of patient education or any other risk-mitigation strategies for prescription opioids. Given the increasing demands placed on physicians in primary care, evidence will be essential to helping physicians prioritize as they put these guidelines into practice.…”
Section: Introductionmentioning
confidence: 99%
“…The exemplar physicians are more likely to use 5 strategies to support patient behavior change: emphasizing patient ownership, partnering with patients, identifying small steps, frequent follow-up visits to cheer success and/or problem solve, and showing caring and concern for patients. 12 The potential constraints of a don't ask/don't tell approach are identified by Metheney and colleagues in an Internet study of men who have sex with men. They find that patients' disclosure of sexual identity to their clinicians is associated with higher rates of routine HIV testing and hepatitis A and B vaccinations.…”
mentioning
confidence: 99%